Connective tissue changes in patients with rectal prolapse - Smyth, EAE (2012)
Rectal prolapse is a common and distressing condition in which the rectum either protrudes externally or telescopes insides itself (intussceception) resulting in evacuatory dysfunction. It has traditionally been viewed as being a disorder of multiparous women who sustain pelvic floor injury during childbirth. However, this explanation fails to account for the occurrence of the condition in nulliparous females, males and children. This thesis seeks to study the relationship between connective tissue changes and the development of rectal prolapse. Participants with rectal prolapse were prospectively recruited to the study (n=105) control tissue was taken from individuals undergoing colonic cancer surgery (n=12). Individuals were assessed for their connective tissue status and grouped according to parity and gender. Analyses focussed on presenting demographics and surgical outcomes in patients with respect to connective tissue status, changes in the extracellular matrix in relation to prolapse, systemic change in connective tissue components. It was found that a proportion of patients have heritable predisposition to altered connective tissue biology in that they had benign joint hypermobility syndrome. These patients typically presented younger and had higher surgical re-intervention rates than those with normal connective tissue status. The extracellular matrix had a number of changes in association with the condition, collagen types 1 and 3 were altered in comparison to control and overall increase in the elastic fibres of the pelvic connective tissues was noted. Alterations in the elastic fibres within the dermis of patients were also identified and suggests that a systemic disorder of connective tissue may account for the development and progression of the condition in some individuals. The pelvic connective tissues themselves were noted to have a number of changes with respect to the disorder, an increase in MMP 1 was noted and this was linked to a reduction in connective tissue supports surrounding the rectum. The growth factor TGF β may play a role in modulating this process and a reduction in the expression of this growth factor was found to be associated with the development of external prolapse. We found that cellularity was increased in response to the process of prolapse in females, but in males this process was attenuated. In addition it was also noted that in some females the cells did not differentiate to the type normally identified in the pelvic connective tissues. The experimental findings suggest that in some individuals a combination of a systemic connective tissue disorder, altered collagen ratios and an environment favouring tissue degradation may account for the development and progression of rectal prolapse.